The Influence of Situational Leadership Style and Big Five Personality on Organizational Commitment - Siswanto, Iwan; Muntholib, Muntholib; Jailani, M. Syahran (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the empirical information on the influence of situational leadership style and big five personality which is determined as the independent variable, and organizational commitment is determined as the dependent variable. This study uses a quantitative approach, with a sample of 145 state Madrasah Aliyah teachers in Riau province and taken using proportional random sampling technique. All data were analyzed using SPSS version 25.0. The results showed that; (1) there is a direct influence of situational leadership style on organizational commitment, (2) there is a direct influence of big five personality on organizational commitment, (3) there is a simultaneous influence of situational leadership style and big five personality on organizational commitment.